ẢNH HƯỞNG CỦA BIẾN DẠNG KÉO DỌC TRỤC ĐẾN TÍNH DẪN ĐIỆN CỦA ỐNG NANÔ CÁC BON ĐƠN LỚP - Trường, Đỗ Văn; Hưng, Nguyến Tuấn (Vietnam Journal of Science and Technology, 2012)
EFFECT OF AXIAL STRAIN ON ELECTRIC PROPERITES OF SINGLE-WALLED CARBON NANOTUBE Carbon nanotubes (CNTs) have been attracting attention because of their characteristic mechanical and electronic properties. A single-walled carbon nanotube (SWCNT) can stretch in the axial direction at 29% strain without any bonds breaking. In this study, the focus is put on the effect of axial strain on electronic properties of SWCNT. The relaxation of atomic conﬁguration is determined by the molecular dynamics simulation based on Brenner’s interatomic potential. The obtained bandgap shows that SWCNT remains either metallic or semiconducting, or transits from metallic to semiconducting depending on the axial strain.